Persistent sciatic artery aneurysm: A rare cause of acute limb ischemia - Pranay Pawar; Achintya Sharma; M K Ayyappan; Radhakrishnan Raju (CHRISMED Journal of Health and Research, 2018)
Persistent sciatic artery (PSA) is a rare but pertinent clinical entity that may pose a threat to the viability of the lower extremity. The incidence of PSA has been estimated to be between 0.01% and 0.05%. PSAs are prone to high incidence of aneurysm formation, thrombosis, distal embolization, and rupture. Early detection of a PSA as the main vascular supply to the lower limb helps in early surgery and avoids potential severe complications such as limb ischemia. We report a case of a female patient who was diagnosed with a case of lumbar disc compression and sciatica but had a PSA aneurysm with thrombosis and distal embolization leading to acute limb ischemia.